2016
DOI: 10.1590/1518-8345.1294.2829
|View full text |Cite
|
Sign up to set email alerts
|

The use of a metronome during cardiopulmonary resuscitation in the emergency room of a university hospital

Abstract: Objective:to compare the rate of return of spontaneous circulation (ROSC) and death after cardiac arrest, with and without the use of a metronome during cardiopulmonary resuscitation (CPR). Method:case-control study nested in a cohort study including 285 adults who experienced cardiac arrest and received CPR in an emergency service. Data were collected using In-hospital Utstein Style. The control group (n=60) was selected by matching patients considering their neurological condition before cardiac arrest, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
3
0
4
Order By: Relevance
“…They did not find any differences between groups with and without metronome use related to the rates of return of spontaneous circulation and death. [ 6 ] However, they did not investigate the effect of quality criteria on survival between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They did not find any differences between groups with and without metronome use related to the rates of return of spontaneous circulation and death. [ 6 ] However, they did not investigate the effect of quality criteria on survival between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported different results regarding metronome-guided CPR quality because they differ in their methods and study group characteristics. [ 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos em sua maioria foram utilizados como metodologia a aplicação de questionários, de modo que seus resultados refletem possíveis estratégias de organização, os mesmos com questões relacionadas a manobras de ventilação em paciente não intubados, vias de administração de medicamentos, posicionamento correto das mãos durante a compressão cardíaca externa, (MOURA et al, 2019); sobre a primeira conduta frente ao paciente com sinais clínicos de PCR (BARROS; NETO, 2018); ventilações, uso de epinefrina, punção venosa e abertura de vias aéreas (BOTELHO et al, 2016).…”
Section: Discussionunclassified
“…Nesse sentido, a análise e avaliação da prática só é considerada um mecanismo complementar da educação, quando conduzida com rigor técnico científico (LUCAS et al, 2018). Para levantar o questionamento para melhoria dessa prática, cita-se a realização das intervenções nos ambientes de atendimentos diante da preconização da AHA na PCR, consistindo em compressões torácicas, ventilação, punção venosa, além da abertura de vias aéreas e uso de medicações (BOTELHO et al, 2016;MAURICIO et al, 2018). E para realização das medicações, Lucas et al, (2018) refere-se que a via de administração intraóssea é a menos utilizada, considerando assim a de maior acesso à via intravenosa, por necessidade de interesse por especializações e treinamentos, além deste, retrata que as instituições não possuírem materiais adequados.…”
Section: Discussionunclassified
See 1 more Smart Citation